How do you differentiate f(x)=sin(x^2 cos x) f(x)=sin(x2cosx) using the chain rule?

1 Answer
Oct 28, 2015

When you finish using the Chain Rule the derivative is

f'(x)=-xcos(x^2cos(x))[xsin(x)-2cos(x)]

Explanation:

Take the derivative of the outside

h(x)=sin(x^2cos(x))

h'(x)=cos(x^2cos(x))

Take the derivative the of the inside, use the product rule

g(x)=x^2cos(x)

g'(x)=x^2(-sin(x))+2x(cos(x))

g'(x)=-x^2sin(x)+2xcos(x)

Multiply the derivative of the outside and inside

f'(x)=cos(x^2cos(x))[-x^2sin(x)+2xcos(x)]

Factor out (-x)

f'(x)=-xcos(x^2cos(x))[xsin(x)-2cos(x)]